2020
DOI: 10.1111/ppl.13068
|View full text |Cite
|
Sign up to set email alerts
|

A novel microRNA, SlymiR208, promotes leaf senescence via regulating cytokinin biosynthesis in tomato

Abstract: Leaf senescence is a highly‐programmed developmental process during the plant life cycle. Cytokinin (CK) has been widely acknowledged as a negative regulator to delay leaf senescence. MiRNAs play key roles in a variety of developmental and physiological processes through negatively regulating their target gene expression. However, to date, the roles of microRNAs (miRNAs) in CK biosynthesis remain unclear, and the knowledge on miRNA regulation of leaf senescence is still very limited. Isopentenyltransferases (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Overexpression of FPS1S (Farnesyl diphosphate synthase) leads to the declined endogenous zeatin-type CK with a concomitant senescence-like phenotype in Arabidopsis (Masferrer et al, 2002 ). SlymiRNA208 suppresses the post-transcriptional expression of SlIPT2 and SlIPT4 in tomato, resulting in the premature leaf senescence in the SlymiRNA208 -overexpressing plants by reducing the endogenous concentration of CKs (Zhang et al, 2020b ). APT1 (Adenine phosphoribosyl transferase 1), which catalyzes the CK conversion from free bases to nucleotides, acts as a positive regulator of leaf senescence.…”
Section: Plant Hormones That Delay Leaf Senescencementioning
confidence: 99%
“…Overexpression of FPS1S (Farnesyl diphosphate synthase) leads to the declined endogenous zeatin-type CK with a concomitant senescence-like phenotype in Arabidopsis (Masferrer et al, 2002 ). SlymiRNA208 suppresses the post-transcriptional expression of SlIPT2 and SlIPT4 in tomato, resulting in the premature leaf senescence in the SlymiRNA208 -overexpressing plants by reducing the endogenous concentration of CKs (Zhang et al, 2020b ). APT1 (Adenine phosphoribosyl transferase 1), which catalyzes the CK conversion from free bases to nucleotides, acts as a positive regulator of leaf senescence.…”
Section: Plant Hormones That Delay Leaf Senescencementioning
confidence: 99%
“…Indeed, the ectopic expression of the sly-miR208 precursor ( 35S::pre-miR208 ) increased the levels of sly-miR208 and reduced the transcript levels of SlIPT2 and SlIPT4 in leaves. Moreover, RLM-RACE revealed that SlIPT2 and SlIPT4 encoding transcripts undergo sly-miR208-guided cleavage in the leaves of 35S::pre-miR208 plants, further supporting their targeting by this putative miRNA [ 101 ]. However, further research is required to confirm that SlIPT2 and SlIPT4 are negatively regulated by the endogenous sly-miR208 and to establish the biological significance of this regulation for cytokinin-mediated tomato development.…”
Section: The Functions Of Tomato Mirnasmentioning
confidence: 99%
“…miR398 participates in regulating leaf senescence by post-transcriptional regulation of ASCORBATE PEROXIDASE 6 ( APX6 ) ( Chen et al, 2021 ). SlymiR208 regulates leaf senescence by controlling the expression of isopentenyl transferases SlIPT2 and SlIPT4 ( Zhang Y. et al, 2020 ).…”
Section: Multiple-layers Of Regulation On Leaf Senescencementioning
confidence: 99%